Mapeamento das pesquisas produzidas sobre inequações entre os anos de 2010 a 2019 - Silva, Greg Cruz (2021)
The general objective of this dissertation is to map and analyze Brazilian research in Mathematics Education, which deals with Inequations, between the years 2010 and 2019. It is a mapping that seeks to inventory and systematize scientific production in this area of knowledge. In this way, 23 works were found (19 of which were masters and 4 doctoral), which were categorized into four distinct categories of analysis: Documentary researches formed by works that make documentary or bibliographic analyzes for the study of inequalities; research suggested in basic education, formed by research that dealt with some suggested activity sequence for basic education; Analysis of applications with students, composed of research that had an approach with students of basic education and Analysis of applications with teachers, composed of research that had an approach in the teaching knowledge in initial or continued training. After the records of the works, it was possible to verify some results regarding the teaching and learning of inequalities. With the survey and analysis of the categorized works, the difference between the amount of research that did documentary research or suggestions for teaching without effective application, and the other categories. We also noticed through the results shown by the twenty-four researchers, whose works made up our mapping, that the teaching of inequalities has not been building satisfactory knowledge in students since their basic education, on the contrary they develop misconceptions and a partial knowledge of the notions that compose that field. There is a lack of studies focused on appropriate didactic choices for teaching inequalities to be developed during basic education